Profile of SETS Approach to Improve Student's Critical Thinking Skills During 2015 to 2022 - Diyah Nur Rahmawati; Tarzan Purnomo; Sunu Kuntjoro (IJORER : International Journal of Recent Educational Research, 2022)
Critical thinking skills are one of the skills needed by students in the 21st century. The research aims to describe and analyze the application of the SETS approach in improving students' critical thinking skills in Indonesia. The method used in this study is a qualitative method of secondary data in the form of a literature study based on the results of previous research. The sample in this study was 20 published scientific articles. Based on the analysis of 20 articles analyzed, it can be seen that the SETS approach can improve students' critical thinking skills which include increasing the N-gain value, positive student responses during learning, and student activity. Further research should integrate other innovative learning models with the SETS approach so that they can be used to develop other 21st-century skills.